Iron Rims in Patients With Multiple Sclerosis as Neurodegenerative Marker? A 7-Tesla Magnetic Resonance Study - Dal-Bianco, A.; Schranzer, R.; Grabner, G.; Lanzinger, M.; Kolbrink, S.; Pusswald, G.; Altmann, P.; Ponleitner, M.; Weber, M.; Kornek, B.; Zebenholzer, K.; Schmied, C.; et al. (Frontiers in Neurology, 2021)
Introduction: Multiple sclerosis (MS) is a demyelinating and neurodegenerative disease of the central nervous system, characterized by inflammatory driven demyelination. Symptoms in MS manifest as both physical and neuropsychological deficits. With time, inflammation is accompanied by neurodegeneration, indicated by brain volume loss on magnetic resonance imaging (MRI). Here, we combined clinical, imaging and serum biomarkers in patients with iron rim lesions (IRL), which lead to severe tissue destruction and thus contribute to the accumulation of clinical disability. Objectives: Subcortical atrophy and ventricular enlargement using an automatic segmentation pipeline for 7 Tesla (T) MRI, serum neurofilament (sNfL) levels and neuropsychological performance in MS patients with IRLs and non-IRLs were assessed. Methods: 29 MS patients (15 women, 24 RRMS and 5 SPMS) aged 38 (22-69) years with an Expanded Disability Status Score of 2(0-8) and a disease duration of 11(5-40) years underwent neurological and neuropsychological examinations. Volumes of lesions, subcortical structures and lateral ventricles on 7T MR images (SWI, FLAIR, MP2RAGE, 3D Segmentation Software) and sNfL concentrations using the Simoa SR-X Analyzer in IRL and non-IRL patients were assessed. Results: 1) IRL patients had a higher FLAIR lesion count (p=0.047). Patients with higher MP2Rage lesion volume exhibited more IRLs (p<0.014) and showed poorer performance in information processing speed tested within 1 year using the Symbol Digit Modality Test (SDMT) (p<0.047). 2) Within 3 years, patients showed atrophy of the thalamus (p=0.021) and putamen (p = 0.043) and enlargement of the lateral ventricles (p=0.012). At baseline and after 3 years, thalamic volumes were lower in IRL than in non-IRL patients (p=0.045). 3) At baseline, IRL patients had higher sNfL concentrations (p=0.028). Higher sNfL concentrations were associated with poorer SDMT (p=0.004), regardless of IRL presence. 4) IRL and non-IRL patients showed no significant difference in the neuropsychological performance within 1 year. Conclusions: Compared with non-IRL patients, IRL patients had higher FLAIR lesion counts, smaller thalamic volumes and higher sNfL concentrations. Our pilot study combines IRL and sNfL, two biomarkers considered indicative for neurodegenerative processes. Our preliminary data underscore the reported destructive nature of IRLs.